The plasma levels of 12 cytokines and growth factors in patients with gastric cancer. Issue 19 (May 2018) - Zou, Zhengyun; Zhao, Lianjun; Su, Shu; Liu, Qin; Yu, Lixia; Wei, Jia; Yang, Yang; Du, Juan; Shen, Jie; Qian, Xiaoping; Fan, Xiangshan; Guan, Wenxian; et al.
Abstract : Abstract: To assess the association of plasma cytokines and growth factor levels with clinical characteristics and inflammatory indices in patients with gastric cancer. Plasma samples derived from 99 gastric cancer patients were used for analysis. Levels of interferon (IFN)-γ, tumor growth factor (TGF)-β1, tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p40, IL-12p70, and vascular endothelial growth factor (VEGF) were measured by Luminex suspension array technology. The association between cytokine/growth factor levels and demographic/clinical characteristics was assessed. Correlation between cytokines and growth factor levels was assessed by Pearson's correlation analysis. Male patients had significant higher levels of plasma TNF-α, IL-12p70, IL-4, IL-10, and VEGF as compared with those in women ( P < .05). Plasma levels of TNF-α in older patients with gastric cancer (≥60 years) were higher than those in young patients ( P < .05). Elevated plasma levels of IL-8 and IL-10 were identified as risk factors for increased tumor size (diameter ≥5 cm). Higher plasma levels of TGF-β1 were associated with increased risk of vascular or nerve invasion and advanced tumor stage. The levels of systemic inflammatory markers, including white blood cell counts, neutrophil/lymphocyte proportion, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio (PLR), C-reactive protein and modified Glasgow prognostic score (mGPS) were closely associated with a series of plasma cytokines. A prominent correlation was observed between the plasma IL-12p70 and IFN-γ levels ( r = 0.729, P < .01). Our findings suggest that plasma cytokines and growth factor levels may help predict the development and progression of gastric cancer. Our findings need to be validated by larger studies.